O imperialismo e a dominação burguesa na primeira república brasileira (1889-1930) - Arruda, Pedro Gustavo Fernandes Fassoni (2007)
At the end of XIX century and beginning of XX century, important transformations had occurred in the economy, in society and in Brazilian politics. The agromercantile economy, focused on the export of primary products, had in coffee its main source of foreign exchange. The development of coffee economy, that was constituted as axle of the capitalist accumulation of the period, also demanded the improvement of the transport systems and the infrastructure of services and communications, placing the problem of the concentration and the centralization of capitals. Estimating a certain international division of the work, the imperialism penetrated in Brazil and abroached the most dynamic sectors, exporting capitals and goods and contributing, to a certain extent, for the development of the local industry. Internally, it was verified the political hegemony of coffee bourgeoisie, when farmers constituted the partner-minors of the financial oligarchy and of the high commercial bourgeoisie. The legal political system was adjusted to the modus operandi of the agroexport economy, in which the development of the productive forces was quite unsatisfactory. Despite the bourgeois institucional frame (representative government, separation of powers, economic freedom, guarantee of the private property, free work etc.), there was a weak development of the capitalism in terms of production. The excludent liberalism of the First Republic, that had excluded most of the population of the political partcipation in strict sense, it was a consequence of an extremely closed system, that practically prevented any alteration in the balance of power within the established rules, formally or tacitly. The ideology of a essentially agriculturist country was one of founded way to confer legitimacy to a politicaleconomic model which condemned the country to the delay and to the subordination front of the great imperialist powers